What are ILRI and BecA and how do they work together? - International Livestock Research Institute (International Livestock Research Institute, 2009)
November 4 2009, Gabrielle Persley, senior advisor to the director general of ILRI, explains what ILRI and BecA are and how the two compliment each other while working with other organizations to improve agriculture in Africa and other developing regions. The senior advisor also mentions recent developments in ILRI and BecA including; facility upgrades co-financed with the Canadian International Development Agency (CIDA); an East Coast Fever vaccine produced by ILRI; and research to improve and protect sorghum productivity in Africa and other developing regions.